Social media influences the process of vocabulary learning in Kurdish EFL university students - MAHMOOD, Hemn Mohammed Ali; Zanyar Nathir GHAFAR; Azeez Abdulkarim MUHAMMED; Sirma Sirwan; Roza Abdul KARIM (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2024)
This study aimed to investigate the role of social media in vocabulary development and language acquisition among Kurdish EFL university students. It sought to demonstrate the benefits of using social media to increase vocabulary and acquire new languages while also providing evidence of the significance of social media platforms in this process. A legitimate market research approach was employed to determine the level of language acquisition among English language department students at Halabja University and the role of social media in this context. The quantitative method was used, and a survey questionnaire was designed after getting validity and reliability; 120 participants were selected from Halabja University through Google Forms. The findings suggest that social media is a powerful tool for vocabulary learning among Kurdish EFL university students. However, further research is necessary to explore the specific features of social media that facilitate vocabulary learning and investigate the effectiveness of different social media platforms. Additionally, future studies should consider incorporating qualitative methods to provide a more nuanced understanding of the impact of social media on language acquisition among Kurdish EFL university students.